FACTORS AFFECTING SUSPECTED MEASLES IN TODDLERS IN KEDUNGWARU DISTRICT, TULUNGAGUNG REGENCY IN 2023: Faktor-faktor yang Mempengaruhi Suspek Campak pada Balita di Kecamatan Kedungwaru Kabupaten Tulungagung Tahun 2023 - Rokhma, Bella Ainur; Azzahro, Qiara Hasna; Hendrati, Lucia Yovita (Universitas Airlangga, 2026)
Background: Measles cases worldwide are still a serious concern, especially the increasing mortality rate. In 2021, 128,000 people lost their lives due to measles, and the number increased to 136,000 in 2023, with the highest death rate in toddlers. Purpose: To determine the relationship between the timeliness of measles immunization, maternal knowledge, and maternal attitudes towards suspected measles in toddlers in Kedungwaru District, Tulungagung Regency. Methods: A case-control study design was used, with a sample of 42 toddlers: 12 in the case group (measles suspects) and 30 in the control group (not measles suspects). Data were analyzed using bivariate binary logistic regression to examine the relationship between each independent variable and the dependent variable, and multivariate analysis to identify the variables most strongly associated with the incidence of measles suspects. Results: There is a significant effect between the timeliness of measles immunization, maternal knowledge, and maternal attitudes towards the incidence of measles suspects (p-value=0.02; OR=6.00 for timeliness of immunization; p-value=0.03; OR=5.18 for maternal knowledge; p-value=0.02; OR=5.50 for maternal attitudes). However, the children's room density variable (p = 0.31) and ​​the ventilation area in children's rooms (p=0.50) do not show a significant effect. Conclusion: The timeliness of measles immunization, maternal knowledge, and maternal attitude have a significant effect on suspected measles in toddlers, with the timeliness of immunization as the most dominant factor, while child's room density and the width of the room's ventilation do not have a significant effect.